Subvencioniranje tujih naložb - Jus, Miran (Naše gospodarstvo, 2006)
CEECs have triggered the phenomenon of FDI incentives. The aim is to speed up evolutional catch-up to the most developed countries. Therefore, a plethora of financial, fiscal and other incentives with certain traps appeared. To avoid them, a thorough consideration of some basic principles of subsidising FDIs is required. However, Slovenian FDI incentive schemes do not lag behind those of their competitors. Even so, their intensity is much too weak. Numerous authors point to the problem of insufficient research concerning the efficiency of FDI subsidies and stress the need for more intensive investigation of their economic impacts. Moreover, investigation should be focused primarily on cost-benefit analysis of subsidies granted.
Keywords: tuje investicije; direktne investicije; subvencije; subvencioniranje; stroški; tax; davki